Effect of Cultivation Temperature on Elastic, Fibrinogenolitic, and Collagenase Activity of Marine Bacteria Bacillus atrophaeus 08, Bacillus licheniformis 043, and Bacillus subtilis 248 - Gudzenko, O.V.; Varbanets, L.D.; Ivanytsia, V.O.; Гудзенко, О.В.; Варбанець, Л.Д.; Іваниця, В.О. (PH "Akademperiodyka" of the NAS of Ukraine, 2025)
Marine microorganisms are the main suppliers of vital organic compounds in the complex ecosystem of the World Ocean thanks to the expression of a wide range of unique enzymes, including proteases. The activity of proteases depends on both the taxonomic affiliation of the strain and the source and place of isolation of the microorganism. Environmental factors of bacteria, such as water salinity, its temperature, pressure, and illumination, largely determine both the composition and the physicochemical properties and substrate specificity of the enzymes produced by them. Since not only the temperature of the residence of microorganisms but also the temperature of their cultivation can significantly affect the activity, the purpose of the work was to determine the optimal cultivation temperatures of producers, necessary to achieve the maximum elastase, fibrinogenolytic, and collagenase activities of the studied strains Bacillus atrophaeus 08, Bacillus licheniformis 043, and Bacillus subtilis 248, which were isolated from different depths of the Black Sea. Methods. The objects of research were three strains: Bacillus subtilis 08, Bacillus licheniformis 043, and Bacillus subtilis 248, which were isolated from bottom sediments from 3 points at depths of 888–2080 m in the Black Sea. Cultures were grown at a temperature of 12, 28, and 42 °C with a rotation speed of 210 rpm for 5 days. At the end of fermentation, the biomass was separated by centrifugation at 5000 g for 30 min. Methods of determining proteolytic (elastolytic, fibrinogenolytic, and collagenase) activity in the culture liquid supernatant were used. Results. Although the studied cultures were isolated from almost the same depth: Bacillus atrophaeus 08, Bacillus subtilis 248 (1499 m), and Bacillus licheniformis 043 (1537 m), the supernatants of their culture liquids showed different enzymatic activity depending on  temperature and growth dynamics. So, for Bacillus atrophaeus 08, the highest elastase and collagenase activities were detected at  28 °C on the second day of cultivation, while fibrinogenolytic activity was detected at 12 °C on the second day of cultivation. The maximum elastase and collagenase activites of Bacillus licheniformis 043 were manifested at  28 °C on the fourth and second day of cultivation, respectively. The highest fibrinogenolytic activity was at 42 °C on the second day of cultivation. When studying Bacillus subtilis 248, it was shown that the maximum elastase activity is achieved at  12 °C on the second day of cultivation, the highest fibrinogenolytic activity was noted at 28 °C on the fourth day of cultivation, and to achieve maximum collagenase activity, it is necessary to grow at 42 °C for four days. Conclusions. The temperature of cultivation of microorganisms plays a significant role in achieving maximum proteolytic activity. Choosing the optimal growing temperature allows for increasing elastase, fibrinogenase, and collagenase activities by several times. It was established that the dynamics of synthesis in different strains is significantly different.